2019
DOI: 10.1039/c8ra10048a
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on extracellular polymeric substances (EPS) and phosphorus accumulating organisms (PAOs) for phosphorus release of anaerobic sludge

Abstract: Phosphorus (P) is an essential element for living organisms and anaerobic sludge is an attractive source for P recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For example, P-PO 4 3− in EPS was found to be just 5 mg/gVSS in one study, which was much lower than that of the WAS cell content (∼60 mg/gVSS). 12 Thus, dosing with ADC is a logical method to recover CH 4 or VFAs with low associated N and P release, and this is further demonstrated below.…”
Section: Was Fermentation By Dosing With Adcmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, P-PO 4 3− in EPS was found to be just 5 mg/gVSS in one study, which was much lower than that of the WAS cell content (∼60 mg/gVSS). 12 Thus, dosing with ADC is a logical method to recover CH 4 or VFAs with low associated N and P release, and this is further demonstrated below.…”
Section: Was Fermentation By Dosing With Adcmentioning
confidence: 95%
“…11 N (such as protein and amino sugar) and P (such as DNA and cytomembrane) are known to be mainly stored within the microbial cell, although these nutrients are rather low in EPS. 12 For example, Liu et al reported that the released protein increased notably from 325 to 988 mg/L after dosing lysozyme in WAS. 13 Soluble DNA also increased from 7 to 34 mg/L by the cation exchange resin (CER)-induced hydrolysis of WAS.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a major part of sludge, extracellular polymeric substances (EPS) play a significant role in phosphorus removal through preserving orthophosphate, pyrophosphate, and polyphosphate. Furthermore, some phosphate precipitates adsorbed or formed in situ inside sludge might also be associated with EPS . Phosphate minerals, such as particles rich in magnesium and phosphorus or calcium and phosphorus, were detected in EPS extracted from various sludge systems. , In addition, struvite was also observed in the isolated sludge EPS after the reaction with ammonium, although this qualitative characterization could not confirm that the struvite formation was due to induced precipitation by EPS, as struvite could also be present in the original EPS.…”
Section: Introductionmentioning
confidence: 99%
“…Acetate and propionate are the typical volatile fatty acids (VFAs) in sewage or municipal wastewater, which are key carbon sources for the EBPR process [19,20]. Temperatures higher than 20 °C were generally reported as unfavorable to the EBPR process, so the EBPR technique might not be suitable for tropical climates with temperatures above 30 °C [21,22,23,24]. Furthermore, the content and composition of LB-EPS and TB-EPS as well as their roles in biological phosphorus removal might also be influenced by the type of organic substrate and the temperature.…”
Section: Introductionmentioning
confidence: 99%